The Health Level Analysis of Bank Jateng During The Covid-19 Pandemic with The Risk-Based Bank Rating Method - Mulyono; Hastuti, Tuti (Journal of Management Research and Studies, 2023)
Bank Jateng has a central role in carrying out the regional mission to support the acceleration of economic growth, especially during the covid-19 pandemic where many business sectors were unable to survive and some of them even went bankrupt. But on the other hand, Bank Jateng is also required to be able to maintain the level of bank health in all conditions. The purpose of this study is to determine the health level of Bank Jateng during the covid -19 pandemic. This type of research is descriptive quantitative with a research sample period during the covid-19 pandemic, namely 2020-2021. The analysis technique uses a risk approach (Risk-based Bank Rating) which includes risk profile ratio analysis factors (risk profile); corporate governance (GCG); income (profitability); and capital ratios (capital), which are abbreviated as RGEC. The results showed that during the covid -19 pandemic, Bank Jateng was included in Composite Rating 1 (PK-1), which reflects the general condition of Bank Jateng as "very healthy", so it is considered very capable of facing significant negative effects from changes in business conditions and other external factors.